Explicit strategy-instruction and the development of higher-order thinking skills in reading comprehension in a primary ESL classroom / Saw Beng Hong - Saw, Beng Hong (2012)
Effective reading instruction in the early grades is the key to creating strong, competent readers. Hence, explicit strategy-instruction can be seen as a powerful student-centred approach to develop good learners to engage in divergent thinking. This study was conducted to look into the efficacy of explicit strategy-instruction in reading to develop the higher-order thinking skills in a year-four primary classroom. The focus of the study was on higher-order thinking skills such as predicting, inferencing and personal response. The materials used were from children’s year-four textbooks and literature books supplied by the Curriculum Development Centre of Malaysia. This was carried out to ensure adherence to curriculum guidelines as well as for ease and effectiveness of implementation in the language classroom. Collection of data was through interviews, questionnaires, participant observation, written responses as well as results of pre and post intervention reading tests. The Critical Reading Inventory test was administered to measure participants’ critical reading ability pre and post intervention of explicit strategy-instruction. Reading lessons were purposely tailored to create opportunities to enable participants to apply strategies taught. The gains in critical reading ability were assessed based on pre and post reading tests. Results from interviews, questionnaires, participants’ written responses, reading tests revealed that participants critical reading ability did improve in a significant way post intervention of explicit strategy-instruction. To conclude the study is a discussion on the limitations of the study, implications of the study, implications of the study to teachers and also implications for future research.